MODIFICATION TO THE BILGE AND SEA WATER PUMPS FITTED IN 17.5 METRE JINGHA TYPE TRAWLERS. - RANJAN, A (Fishery Technology, 2017)
This paper brings out the difficulties encountered with theBilge and sea water circulating pumps which are fitted anddrawn in series alongwith a fresh water pump in the 17.5 m.fishing trawlers.